New Disruptive Models for the Telecommunications Operators in the New Digital Arena - Armenta, Christian James Aguilar (Law, State and Telecommunications Review, 2019)
Purpose ”“ We know that the new digital ecosystem brings with it the emergence of new services in telecommunications, which in turn entails opportunities and challenges for both operators and regulators. It is essential to know its current status, in order to understand and try to predict the role played by operators in the value chain of new business models, the types of interaction they will have with other stakeholders, as well as the possible regulatory impacts. Methodology/approach/design ”“ To contribute to this end, in this article we present a review of newly created business models, in which operators are the main actors. Findings ”“ After a detailed analysis of the most relevant cases, we present the regulatory challenges they represent today, as well as their potential implications in terms of economic competition.